2014
DOI: 10.1063/1.4890970
|View full text |Cite
|
Sign up to set email alerts
|

Raman scattering analysis of electrodeposited Cu(In,Ga)Se2 solar cells: Impact of ordered vacancy compounds on cell efficiency

Abstract: This work reports the detailed Raman scattering analysis of Cu-poor Cu(In,Ga)Se2 (CIGS) electrodeposited solar cells using different excitation wavelengths. The systematic assessment of cells fabricated with Cu-poor absorbers that were synthesized with different Cu contents has allowed identifying the existence of a quasi-resonant excitation of a Raman peak characteristic of an Ordered Vacancy Compound (OVC) secondary phase when using a 785 nm excitation wavelength. The enhanced sensitivity of the spectra meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 12 publications
5
42
0
Order By: Relevance
“…Under this condition, the increase of this contribution is assigned to the presence of Ordered Vacancy Compound (OVC) phases, as is illustrated in the OVC reference spectra (corresponding to CuIn 3 Se 5 ) in the same figure [24]. Differences between the reference and the absorber spectra correspond to different OVC compositions (OVC phases have several stoichiometries including CuIn 5 Se 8 , CuIn 2 Se 3.5 , and CuIn 1.5 Se 2 ) [24,25]. Although the OVC phases are usually associated with Cu-poor conditions, it was reported that these phases can be also formed close to Cu-Se secondary phases in Cu-rich layers, as those observed in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under this condition, the increase of this contribution is assigned to the presence of Ordered Vacancy Compound (OVC) phases, as is illustrated in the OVC reference spectra (corresponding to CuIn 3 Se 5 ) in the same figure [24]. Differences between the reference and the absorber spectra correspond to different OVC compositions (OVC phases have several stoichiometries including CuIn 5 Se 8 , CuIn 2 Se 3.5 , and CuIn 1.5 Se 2 ) [24,25]. Although the OVC phases are usually associated with Cu-poor conditions, it was reported that these phases can be also formed close to Cu-Se secondary phases in Cu-rich layers, as those observed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Also, the presence of OVC's in the surface detected by this technique (see Fig. 3b) could contribute to the reduction of the density of defects [25,26], enhancing the cell's voltage. Nevertheless, the J sc and FF of the cell are remarkably lower than values expected for this material [27,28].…”
Section: Resultsmentioning
confidence: 99%
“…Depth resolved Raman scattering measurements have already been reported for the analysis of depth composition in-homogeneities in CIGSe [13] as well as for the identification of CuIn(S,Se) 2 quaternary alloys [14]. The use of suitable excitation conditions allows also the very high sensitive detection of secondary phases which could have a strong impact on device efficiency, as Cu-poor ordered compounds [15]. In addition, spectral features of these compounds main Raman peaks are also sensitive to the presence of relevant electronic defects as those related to Se vacancies and Cu interstitials [16].…”
Section: Introductionmentioning
confidence: 98%
“…For these applications, optical spectroscopy based on Raman scattering has already proved its versatility for controlling various important material parameters of the stacks used in thin film solar cells, including crystallinity 8 , absorber and buffer composition 9, 10 , buffer layer thickness 8 , presence of secondary interfacial phases 11, 12 and doping concentration 13 in separate layers, as well as complete devices 8 . This includes also the use of resonant Raman strategies for the high sensitivity assessment of nanometric layers and interfacial regions in the device structure.…”
Section: Introductionmentioning
confidence: 99%